Induction Time And Sedative (Recovery) Time In Closed System Transportation Of Tawes Fish (Barbonymus gonionotus) Anesthetized With Clove Oil At Different Temperatures - Saragih, Debby Dyanessa; Ngangi, Edwin L.A.; Pangkey, Henneke; Sumilat, Deiske Adeliene; Salindeho, Indra R.N.; Kreckhoff, Reni Lusia; Kusen, Diane Joula (Sam Ratulangi University, 2025)
The conservation of tawes fish (Barbonymus gonionotus) is carried out through aquaculture and restocking, where seed transportation is a crucial factor affecting survival rates. Mishandling during transport can increase stress, metabolism, and mortality risk. Reducing stress during transport can be achieved by using natural anesthetic agents such as clove oil (Eugenia aromatica) and low-temperature regulation. This study aims to analyze the effects of clove oil dosage and temperature on the induction time and recovery of tawes fish seeds. The experiment was designed using a completely randomized design (CRD) with two factors: clove oil dosage (0 ppm, 5 ppm, 10 ppm) and temperature (16–19°C and 24–27°C), with 18 experimental units (3 replications). Data were analyzed using ANOVA (JMP-SAS). The results showed that combining clove oil and temperature significantly affected induction and recovery times. The 10 ppm clove oil treatment at 16–19°C resulted in the fastest induction time, while the 0 ppm treatment at 24–27°C led to the fastest recovery. The interaction between these factors demonstrated that clove oil significantly influenced the fish's response to temperature changes. Keywords: tawes fish seed, transportation, temperature, clove oil, induction, sedative. Abstrak Pelestarian ikan tawes (Barbonymus gonionotus) dilakukan melalui budidaya dan restocking, di mana transportasi benih menjadi faktor krusial yang memengaruhi tingkat kelangsungan hidupnya. Kesalahan dalam penanganan dapat meningkatkan stres, metabolisme, dan risiko kematian benih. Upaya menekan stres selama transportasi dilakukan dengan penggunaan agen pembius alami, seperti minyak cengkih (Eugenia aromatica) dan pengaturan suhu rendah.Penelitian ini bertujuan menganalisis pengaruh dan dosis minyak cengkih serta suhu terhadap waktu induksi dan pemulihan (recovery) benih ikan tawes. Percobaan menggunakan rancangan acak lengkap (RAL) dengan dua faktor: dosis minyak cengkih (0 ppm, 5 ppm, 10 ppm) dan suhu (16–19°C dan 24–27°C), dengan 18 unit percobaan (3 ulangan). Data dianalisis menggunakan ANOVA (JMP-SAS).Hasil penelitian menunjukkan bahwa kombinasi minyak cengkih dan suhu berpengaruh signifikan terhadap waktu induksi dan pemulihan benih. Perlakuan 10 ppm minyak cengkih pada suhu 16–19°C menghasilkan waktu induksi tercepat, sedangkan tanpa minyak cengkih pada suhu 24–27°C mempercepat pemulihan. Interaksi kedua faktor ini menunjukkan bahwa minyak cengkih secara nyata mempengaruhi respons ikan terhadap perubahan suhu. Kata kunci: benih tawes, transportasi, suhu, minyak cengkih, induksi, sedatif.